2011
DOI: 10.1002/hed.21653
|View full text |Cite
|
Sign up to set email alerts
|

Manganese superoxide dismutase and glutathione peroxidase as prognostic markers in patients with buccal mucosal squamous cell carcinomas

Abstract: MnSOD and GPx are significant prognostic factors for favorable survival in patients with buccal mucosal SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…For example, the correlation between multiple oxidative stress biomarkers and breast cancer, squamous cell carcinomas, leukemia, and colorectal cancer was found (106,221,390,400). As discussed later in more detail, there are data showing that diet composition, especially the supplementation with antioxidants, influence the plasma or urinary levels of oxidative stress markers (see sections VI and VII) (48,101,232,247).…”
Section: The Limitations Of Oxidation Markers In Usementioning
confidence: 97%
See 2 more Smart Citations
“…For example, the correlation between multiple oxidative stress biomarkers and breast cancer, squamous cell carcinomas, leukemia, and colorectal cancer was found (106,221,390,400). As discussed later in more detail, there are data showing that diet composition, especially the supplementation with antioxidants, influence the plasma or urinary levels of oxidative stress markers (see sections VI and VII) (48,101,232,247).…”
Section: The Limitations Of Oxidation Markers In Usementioning
confidence: 97%
“…A good example of such enzyme that has compartment-specific isoforms is SOD, and changes in the cytosolic Cu/ZnSOD (SOD1), mitochondrial MnSOD (SOD2), or extracellular SOD (EcSOD; SOD3) activity or expression can be correlated to ROS levels. Elevated MnSOD levels were found in tissues of patients with gastric carcinomas and adenomas (182) as well as squamous cell carcinomas, whereas no significant changes in Cu/ZnSOD were detected (106,391). By contrast, increased Cu/ZnSOD activity was found in tissue samples from patients with colorectal cancer (331), in leukemia patients (400), and in patients with breast cancer (22,288).…”
Section: Compartment-specific Ros Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been conflicting reports on the effects of n-3 polyunsaturated fatty acid supplementation on oxidant/antioxidant status in humans (45,46). Several studies have observed significant associations in head and neck cancer between SOD and GPx activity and better disease-specific survival and postoperative RT (47), between manganese SOD and tumor migration and invasion (48), and between the loss of GPx expression and tumor chemoresistance (49), all important prognostic factors for survival. There is also a deranged antioxidant defense system due to significantly low levels of TAC (50) and higher levels of nitric oxide and GST in these cancer patients, with a significant increase after RT (51).…”
Section: A B C D Ementioning
confidence: 99%
“…The literature indicates an overwhelming evidence of the negative influence of oxidative stress and MnSOD in inflammation and cancer (Fu et al, 2011;Li et al, 2011;Suzuki et al, 2001). Because Mn and iron (Fe) play an important role in the biosynthesis of MnSOD (Hassan & Schrum, 1994), data on the dietary intake of Mn may provide valuable information on possible biochemical requirements for the production and upregulation of MnSOD.…”
Section: Ethnicity and Dietary Antioxidant Intakementioning
confidence: 99%